2023
DOI: 10.3389/fphys.2023.1146076
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal load in the Wingate Anaerobic Test is not depend on number of sprints included in mathematical models

Abstract: Determining the optimal load (OPTLOAD) in measuring mechanical peak power output (PPO) is important in assessment of anaerobic fitness. The main goals of this study were: 1) to examine estimated optimal load and PPO based on a force-velocity test and 2) to compare the PPO from the previous method with the Wingate Anaerobic Test (WAnT). The study involved 15 academic male athletes, aged 22.4 ± 2.3 (years), height 178.9 ± 6.8 (cm), and body weight 77.9 ± 12.2 (kg). They performed the 30-s WAnT (7.5% of body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Zemková et al (44) showed that the peak rate of force development obtained from MVIC of the back muscles may be predictive of power performance during a lifting task. Both of these factors can potentially establish a relative load factor corresponding to individual characteristics, like sex, age, or training level, because previous studies have shown a correlation between force-velocity and powervelocity development (31,45).…”
Section: Discussionmentioning
confidence: 99%
“…Zemková et al (44) showed that the peak rate of force development obtained from MVIC of the back muscles may be predictive of power performance during a lifting task. Both of these factors can potentially establish a relative load factor corresponding to individual characteristics, like sex, age, or training level, because previous studies have shown a correlation between force-velocity and powervelocity development (31,45).…”
Section: Discussionmentioning
confidence: 99%